2007
DOI: 10.1105/tpc.106.048033
|View full text |Cite
|
Sign up to set email alerts
|

The Acyltransferase GPAT5 Is Required for the Synthesis of Suberin in Seed Coat and Root of Arabidopsis

Abstract: Suberin and cutin are fatty acid-and glycerol-based plant polymers that act as pathogen barriers and function in the control of water and solute transport. However, despite important physiological roles, their biosynthetic pathways, including the acyl transfer reactions, remain hypothetical. We report the characterization of two suberin mutants (gpat5-1 and gpat5-2) of Arabidopsis thaliana GPAT5, encoding a protein with acyl-CoA:glycerol-3-phosphate acyltransferase activity. RT-PCR and b-glucuronidase-promoter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
405
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 371 publications
(450 citation statements)
references
References 82 publications
27
405
1
2
Order By: Relevance
“…1, A-C). This observation is reminiscent of GPAT5 promoter activity shown both with YFP (Molina et al, 2008) and GUS (Beisson et al, 2007) reporters, and to CYP86A1 expression (data not shown). As desiccation proceeds, strong ASFT expression was also observed at the chalazal region (Fig.…”
Section: Asft Is Expressed In Tissues Of Seeds and Roots Where Suberimentioning
confidence: 92%
See 3 more Smart Citations
“…1, A-C). This observation is reminiscent of GPAT5 promoter activity shown both with YFP (Molina et al, 2008) and GUS (Beisson et al, 2007) reporters, and to CYP86A1 expression (data not shown). As desiccation proceeds, strong ASFT expression was also observed at the chalazal region (Fig.…”
Section: Asft Is Expressed In Tissues Of Seeds and Roots Where Suberimentioning
confidence: 92%
“…These genes encode the acyltransferase GPAT5 (Beisson et al, 2007) and the cytochrome P450 monooxygenase CYP86A1, a fatty acyl v-hydroxylase (Li et al, 2007a;Hö fer et al, 2008). Using these two genes as the bait set, correlation analysis of gene expression across all microarray data sets (Wei et al, 2006) identified a number of other genes with a strong correlation (Supplemental Table S1), including two members of the BAHD gene family, AT5G41040 (ASFT) and AT5G63560.…”
Section: Bahd and Cyp86b1 Genes Correlated With The Expression Of Submentioning
confidence: 99%
See 2 more Smart Citations
“…Suberin often includes substantial amounts of saturated monomers with chain length .C20 (Kolattukudy, 1980(Kolattukudy, , 2001Bernards, 2002;Schreiber et al, 2005). Analyses of Arabidopsis tissues expected to be enriched in suberin, namely, roots and seed coats, have shown typical suberin monomer compositions (Franke et al, 2006;Molina et al, 2006;Beisson et al, 2007). A substantial portion of the hydroxycinnamic acids of suberin are believed to be cross-linked (Bernards et al, 1995;Bernards, 2002).…”
mentioning
confidence: 99%